Case report: A family of atypical hemolytic uremic syndrome involving a CFH::CFHR1 fusion gene and CFHR3-1-4-2 gene duplication - Tasaki, Yuko; Tsujimoto, Hiroshi; Yokoyama, Tadafumi; Sugimoto, Naotoshi; Kitajima, Shinji; Fujii, Hiroshi; Hidaka, Yoshihiko; Kato, Noritoshi; Maruyama, Shoichi; Inoue, Norimitsu; Wada, Taizo (Frontiers in Immunology, 2024)
Mutations in the complement factor H (CFH) gene are associated with complement dysregulation and the development of atypical hemolytic uremic syndrome (aHUS). Several fusion genes that result from genomic structural variation in the CFH and complement factor H-related (CFHR) gene regions have been identified in aHUS. However, one allele has both CFHR gene duplication and CFH::CFHR1 fusion gene have not been reported. An 8-month-old girl (proband) presented with aHUS and was treated with ravulizumab. Her paternal grandfather developed aHUS previously and her paternal great grandmother presented with anti-neutrophil cytoplasmic antibody-associated vasculitis and thrombotic microangiopathy (TMA). However, the proband’s parents have no history of TMA. A genetic analysis revealed the presence of CFH::CFHR1 fusion gene and a CFHR3-1-4-2 gene duplication in the patient, her father, and her paternal grandfather. Although several fusion genes resulting from structural variations of the CFH–CFHR genes region have been identified, this is the first report of the combination of a CFH::CFHR1 fusion gene with CFHR gene duplication. Because the CFH–CFHR region is highly homologous, we hypothesized that CFHR gene duplication occurred. These findings indicate a novel pathogenic genomic structural variation associated with the development of aHUS.